PEMBANGUNAN SISTEM INFORMASI PELAYANAN MASYARAKAT DESA BERBASIS DIGITAL - Aminuddin; Muhammad Rozahi Istambul; Hari Supriadi (Universitas Widyatama, 2022)
The village is the smallest part of the government so that the implementation of various performances must refer to the rules that apply to the government. One of the things that are the obligation of a village is that it is necessary to transparently show its performance to the community in the village concerned. This is nothing but to provide various information that the community needs to know when it will take care of various needs and require approval or recognition from the village as a form of authority in the government. Another very important performance is managed by the village apparatus, namely the service of a certificate which is very much needed by the village community. These various types of certificates, of course, will be one of the requirements for the community to complete their affairs, which indeed often ask for statements from the village. The service information system is a system that has a very important role in government and the development of population data administration, which is directed at fulfilling the rights of every citizen. In line with the direction of carrying out population data collection, population registration and civil registration as population sub-pillars need to be organized as well as possible, in order to provide benefits in improving governance and development, where population data management is the responsibility of the Regency/City Government, in its implementation starting from Rt/Rw/Village and Sub-district as the spearhead of population data collection. Based on the background of the problem above, a digital-based village service information system will be built. The service information system will be used within the scope of Ciwaruga Village, Parongpong District, West Bandung Regency.